Designing Physical Learning Environment For Restrictive And Repetitive Behaviors In Children With Autism (Architecture Image Studies, 2025)
Restrictive and Repetitive Behaviors (RRBs) are the most prominent problematic characteristics in children with autism. Neurophysiological studies indicate that environmental stimuli are the main triggers of RRBs, making the physical environment crucial for managing RRBs and enhancing these children’s participation in daily activities. However, standardized guidelines for designing autism-friendly learning environments to address RRBs remain lacking.This quantitative study used a survey method to explore the relationship between RRBs in autistic children and physical learning environment design. A total of 100 participants were involved, with data entered and analyzed via SPSS; Pearson’s correlation coefficient was used to examine variable relationships. Results show a significant, close association between RRB severity and physical learning environment design. These findings are expected to provide useful references for optimizing autism learning environments in China.